THE ROLE OF LABOUR DIVERSITY IN DRIVING INNOVATION AND ACCELERATING ECONOMIC GROWTH - Hotmaria Hertawaty Sijabat (CV. Adiba Aisha Amira, 2024)
The role of workforce diversity in driving innovation and accelerating economic growth refers to the positive contribution that a diverse work environment makes to creativity, the development of new ideas, and increased productivity within an organisation or the economy as a whole. Workforce diversity includes variations in aspects such as age, gender, ethnic background, education, experience, and perspective. When these different viewpoints and expertise are combined, they create a dynamic that encourages innovative thinking, more effective problem-solving, and the development of more relevant products or services for diverse markets. The innovation that results from this workforce diversity then acts as a catalyst for economic growth. The new products and services developed can open up new markets, increase the competitiveness of companies, and drive job creation. In addition, operational efficiencies improved through innovative approaches can lead to higher productivity and better use of resources. On a broader scale, economies that make effective use of the diversity of their workforce tend to be more resilient, adaptive and able to respond more quickly to global market changes, which in turn accelerates overall economic growth.